2020
DOI: 10.1002/slct.202000705
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Non‐Noble Metal Based Anode Electrocatalyst to Promote Methanol Oxidation Activity in DMFC

Abstract: In this research, electrocatalytic activity of cobalt benzene tricarboxylic acid metal organic framework (Co BTC MOF) and its reduced graphene oxide based composites (rGO/Co BTC) were investigated in an alkaline media for the methanol oxidation reaction (MOR). Metal Organic frameworks (MOF) and their composites were solvothermally prepared and characterized via FTIR, EDX, SEM and XRD. Electrochemical studies were performed by cyclic voltammetry, electron impedance spectroscopy, chronoamperometry and cyclic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…At low content of CH 3 OH, the boosted current response is owing to excess of available OH − ions owing to diffusion-controlled methanol transport process while at high CH 3 OH concentration, excess of methanol limit the OH − adsorption, and reaction intermediates block the active sites and consequently depress the catalytic activity, Fig. 7 b 77 79 .
Figure 7 ( a ) Influence of electrocatalyst deposited quantity, and ( b ) CH 3 OH molarity on the current density response of NiNH 2 BDC MOF/1, 2, 5 wt% reduced graphitic carbon hybrids during the optimization process.
…”
Section: Resultsmentioning
confidence: 99%
“…At low content of CH 3 OH, the boosted current response is owing to excess of available OH − ions owing to diffusion-controlled methanol transport process while at high CH 3 OH concentration, excess of methanol limit the OH − adsorption, and reaction intermediates block the active sites and consequently depress the catalytic activity, Fig. 7 b 77 79 .
Figure 7 ( a ) Influence of electrocatalyst deposited quantity, and ( b ) CH 3 OH molarity on the current density response of NiNH 2 BDC MOF/1, 2, 5 wt% reduced graphitic carbon hybrids during the optimization process.
…”
Section: Resultsmentioning
confidence: 99%
“…It is an effective approach to evaluate MOR activity. Using the formula (E‐E o ), 50 the overpotential is determined. The NiMnCo/NPC composite has a smaller overpotential curve in this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Co BTC 1 wt% rGO composite (2.5 mg) shows good electrocatalytic activity by producing a current density of 130 mA/cm 2 at peak potential of 1.59 V(RHE) along with Tafel slope of 83.6 mV/dec, resistance of 14.75 Ω, and long-term stability for 3500 seconds in 1 M KOH and 2 M methanol solution. 182 Maybodi et al, in 2015, reported nonporous ZIF-8 nanoparticles, synthesized at ambient conditions by using a facile template-free strategy. To decrease the overvoltage of CH 3 OH oxidation on CPE (carbon paste electrode), nickel incorporated ZIF-8 modified carbon paste electrode (Ni/ZIF-8CPE) was fabricated as a reformed electrode.…”
Section: Mof and Mof-derived Materials/ Carbon-based Composites Formentioning
confidence: 99%
“…Spherical shape nanoparticles synthesized through solvothermal technique were characterized through FTIR, SEM, XRD, and EDX, and electrochemical testing was carried out through EIS, CV, and chronoamperometry. Co BTC 1 wt% rGO composite (2.5 mg) shows good electrocatalytic activity by producing a current density of 130 mA/cm 2 at peak potential of 1.59 V(RHE) along with Tafel slope of 83.6 mV/dec, resistance of 14.75 Ω, and long‐term stability for 3500 seconds in 1 M KOH and 2 M methanol solution 182 …”
Section: Materials For a Methanol Oxidation Reactionmentioning
confidence: 99%